2018
DOI: 10.21276/obgyn.2018.4.2.11
|View full text |Cite
|
Sign up to set email alerts
|

A study on risk factors and clinical presentation of ectopic pregnancy

Abstract: Objectives: The present study was designed to study the risk factors of ectopic pregnancy and their clinical presentation. Material and methods: It was a retrospective study with 100 cases of ectopic pregnancy conducted in the Department of Obstetrics and Gynecology, ESIC MC PGIMSR, Rajajinagar, Banglore for a period of 2 years were included. Detailed history suggestive of risk factors for ectopic pregnancy, menstrual and obstetric history was taken. Results: A total of 7200 pregnancies were confirmed during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The present study reports a frequency of 75 patients with ectopic pregnancy (5.5%). In comparison, in an Indian study by Prasanna et al [ 7 ], the frequency of EP was 1.8%, while another Indian study by Nethra et al [ 6 ] reports a frequency of 1.38%. Verma et al [ 2 ] reported frequency of EP to be 2.3%.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The present study reports a frequency of 75 patients with ectopic pregnancy (5.5%). In comparison, in an Indian study by Prasanna et al [ 7 ], the frequency of EP was 1.8%, while another Indian study by Nethra et al [ 6 ] reports a frequency of 1.38%. Verma et al [ 2 ] reported frequency of EP to be 2.3%.…”
Section: Discussionmentioning
confidence: 85%
“…The most common symptom was pain in the abdomen (90.76%), amenorrhea in 79.23% of cases, and bleeding PV in 63.07% of cases. Nethra et al [ 6 ] reported that the majority of women were 21-30 years of age (63%), were multigravida (76%), and had lower socioeconomic status (74%). Amenorrhea, pain in the abdomen, bleeding per vagina, and fainting and syncopal attack were present in 96%, 88%, 78%, and 16% cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations